2021
DOI: 10.22492/ijpbs.7.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal Visits in Prisons Discourse: The Prisoners’ Voice in Malawi

Abstract: The issue of possible provision of prisoners’ conjugal rights in jurisdictions not yet allowing them, such as Malawi, is still an intricate debate amongst the stakeholders. However, the most important stakeholder in the issue, the prisoner, is usually left out of the discourse. This study analyzed the perceptions of randomly sampled 305 prisoners on conjugal visits at one of the central prisons in Malawi. Both qualitative and quantitative data from prisoners’ perceptions were collected and used concurrently. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The inadequacy of resources finding concurs with previous studies conducted in many countries including Malawi (e.g. Kajawo & Nyirongo, 2022;Kajawo, 2019;Kajawo & Johnson, 2023a;2023b;Johnson, 2015;Korzh, 2021). Kajawo and Nyirongo (2022), based on their study conducted at 17 correctional facilities in Malawi, revealed that education was faced with several problems, including shortages of proper classrooms, libraries, laboratories and adequate learning materials such as notebooks, prescribed textbooks and pens.…”
Section: Why Not Us? Experiences Of Incarcerated Women On Education A...supporting
confidence: 88%
See 3 more Smart Citations
“…The inadequacy of resources finding concurs with previous studies conducted in many countries including Malawi (e.g. Kajawo & Nyirongo, 2022;Kajawo, 2019;Kajawo & Johnson, 2023a;2023b;Johnson, 2015;Korzh, 2021). Kajawo and Nyirongo (2022), based on their study conducted at 17 correctional facilities in Malawi, revealed that education was faced with several problems, including shortages of proper classrooms, libraries, laboratories and adequate learning materials such as notebooks, prescribed textbooks and pens.…”
Section: Why Not Us? Experiences Of Incarcerated Women On Education A...supporting
confidence: 88%
“…Consequently, studies report that education opportunities were accessible to inmates at various prison facilities in Malawi (Kajawo, 2019;2022;Kajawo & Nyirongo, 2022;Kajawo & Johnson, 2023a;2023b). In 2020, there were 15 prison facilities offering educational programmes out of 30 in the country (Kajawo & Nyirongo, 2022).…”
Section: Incarcerated Women and Girls Access To Educationmentioning
confidence: 99%
See 2 more Smart Citations